Rantai Pasok Pemasaran Produk Kelompok Tani Di Era Pandemic Covid-19 - Rosali Sembiring; Miguna Astuti; Jenji Gunaedi Argo (Coopetition : Jurnal Ilmiah Manajemen, 2022)
The people of each region always have different characteristics and uniqueness of each, especially between rural communities which tend to be homogeneous and have strong elements of customs compared to urban communities which tend to be heterogeneous and begin to reduce the elements of their customs. Building rural communities through empowerment is the main key to mobilizing the potential of the Indonesian agricultural sector. Surya Tani farmer group is a farmer group located in Mekaragung village, Cigundi village. The farmer group was founded on the initiative of Mr. Deddy, who was diligent as a farmer in the broad and narrow sense. From the results of surveys and interviews with members of the Surya Tani farmer group, the researchers wanted to know how to apply supply chains and market expansion to the marketing of products or crops at the Surya Tani farmer group in Cibadak, Lebak – Banten. Methods of collecting data were observations, interviews and questionnaires to the chairman and members of the Surya Tani farmer group. The data analysis technique was carried out with a descriptive qualitative approach. From the results of the study, it was found that the Surya Tani farmer group had not implemented a supply chain but the Surya Tani farmer group was able to expand the market to market their agricultural products out of the Lebak-Banten area market to the DKI Jakarta main market. However, it is different in the distribution process, which is experiencing delays in delivery due to the implementation of PSBB in the era of the covid-19 pandemic.